10 years experience of the german council of economic experts - Herbert Giersch (Intereconomics, 1973)
Ten years ago, in August 1963, the Federal Republic of Germany set up a Council of Experts on Economic Development. The author — a former member of the Council — makes a resumé of the ten years' experience and the problems connected with the Council.
Keywords: 330; Germany